Anti-melanoma and UV-B protective effect of microbial pigment produced by marine Pseudomonas aeruginosa GS-33. Issue 24 (16th December 2016) - Patil, Sandeep; Paradeshi, Jayasinh; Chaudhari, Bhushan
Abstract: Bioactivity of a microbial pigment, extracted from fermented broth of culture marine Pseudomonas aeruginosa was screened for anticancer activity against human skin melanoma cell line SK-MEL-2. Upon characterisation, the pigment was confirmed as Phenazine-1-carboxylic acid (PCA). The PCA was found effective against SK-MEL-2 cell line at low concentration (GI50 value <10 μg/mL). Reduced cell density and cell shrinkage with typical morphological changes such as rounding of cells with loss/breaking of cell membrane were seen in SK-MEL-2 cells treated with PCA and Adriamycin. The pigment exhibited UV-B protecting activity as calculated by in vitro spectrophotometric assay and potentiated sun protection factor of commercial sunscreen lotion. Moreover, the pigment was non-toxic up to concentration of 100 ppm as assessed erythrocyte haemolysis assay. These results suggest that microbial pigment PCA could be effective and promising in the treatment as well as prevention of melanoma skin cancers. Abstract :